Prevalence of Post-Partum Depression among Health Care Professionals and Its Risk Factors - Ahmed, Asfa; Sultan, Muhammad Omer; Khan, Muhammad Inam; Ahmed, Alisha; Zaheer, Marha; Younis, Ayesha (Biological and Clinical Sciences Research Journal, 2025)
Postpartum depression (PPD) is a prevalent nonpsychotic mood disorder that manifests during the postpartum period, significantly affecting maternal wellbeing, infant development, and family dynamics. Healthcare professionals, owing to their dual burden of occupational stress and maternal responsibilities, are particularly vulnerable to depressive symptoms. Objective: To determine the prevalence of postpartum depression and identify the associated risk factors among healthcare professionals. Methods: A cross-sectional study was conducted on 149 women who were employed as healthcare workers and had experienced pregnancy at least once in their lives. Participants’ scores on the Edinburgh Postnatal Depression Scale were used to screen for PPD. Women were classified as having depressive symptoms if they had an EPDS score of 12 or higher. Information regarding the sociodemographic characteristics, job satisfaction, prenatal mood disturbances, prenatal sleep quality, emotional support from co-workers, prior diagnosis of psychiatric illness, and financial concerns during pregnancy, and perceived family and peer support were considered for bivariate analysis. Results: Out of 149 women, 53% had an EPDS score of 12 or higher, indicating depression. 54.4% of women expressed job satisfaction, while 62% reported overall good health. Prenatal variables associated significantly with EPDS score included mood disturbances, sleep quality, emotional support from co-workers, a prior diagnosis of psychiatric illness, and financial concerns. Postpartum physical difficulties and slow recovery were linked to an increased risk of developing PPD. A higher EPDS score was also linked to caesarean sections and job satisfaction. Conclusion: Prevalence of PPD is slightly higher in women working in healthcare, with implications for both mother and child health. This emphasizes the importance of screening and closely monitoring mothers at high risk of PPD, as well as providing appropriate treatment plans.